Strong Maximal Lq - Lp - estimates for the Solution of the Stokes Equation - Tong, Maoting (Transactions on Engineering and Computing Sciences, 2023)
Suppose that W is a bounded domain in R3 with smooth boundary ¶W of class C3. In this paper we prove that if the initial value u0 ÎD((-D)1/2 ), then there are strong maximal Lq - Lp -estimates for the solution of the Stokes equation (1) for any 1<q<¥，2 £ p<¥. Mathematics Subject Classification (2010). Primary 35Q30, 76D07; Secondary76N10, 47D06.